PENDAMPINGAN PENENTUAN KONSEP TATA KELOLA PEMERINTAH DESA YANG AKUNTABEL DAN TRANSPARANSI - Hartiningsih Astuti; Susilo, Joko Hadi; Endang; Surya Atmaja, Dimas; Alfiyana, Siti; Fatmawati, Dewi (Jurnal Abdi Masyarakat, 2024)
Accountability and transparency in the governance of Mojodelik Village, Gayam District, Bojonegoro Regency, are important aspects to realize effective and accountable village financial management. Based on the Regulation of the Minister of Home Affairs Number 113 of 2014 concerning Village Financial Management, the concept of accountability is implemented through detailed and accurate financial reporting, including the Village Revenue and Expenditure Budget and budget realization reports. Transparency is realized by publishing financial information through bulletin boards and village websites, and involving the community in development decision-making meetings. Although there are obstacles such as limited human resources and technology, and low community participation, the implementation of these principles aims to increase community trust and active participation in monitoring village financial management. Suggestions for increasing accountability and transparency include optimizing the use of information technology, regular training for village officials, and increasing socialization and community participation in the government process. These steps are expected to create a more open, responsive, and responsible governance system in Mojodelik Village.